Model Mitigasi Non Struktural Bencana Banjir di Kecamatan Dayeuhkolot Kabupaten Bandung - Yayu Ratna Wulan; Deddy Mulyadi; Nita Nurliawati (Jurnal Media Administrasi Terapan, 2022)
Dayeuhkolot District is the area with the heaviest impact in the flood disaster that occurred in Bandung Regency, high rainfall during the rainy season is the main factor causing flooding. The larger the disaster victims, the greater the impact that will occur, both directly felt by the community and local government, ironically the above flood disaster management activities are still focused on structural mitigation activities which of course require very large costs. In contrast to structural mitigation, non-structural mitigation is the reduction of the possibility of risk through engineering on human behavior including changes in behavior towards nature. This study uses direct observation in the field observing the mitigation that has been done, making documentation, conducting interviews. All data is processed in a reduced pattern and re-verified to produce a conclusion. The method of non-structural flooding from Coppola is a study that is specifically discussed in this study.